2009
DOI: 10.1177/1934578x0900400726
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Composition and in Vitro Antibacterial Activity of the Essential Oil of Minthostachys Mollis (Kunth) Griseb Vaught from the Venezuelan Andes

Abstract: Chemical constituents of the essential oil from the leaves of Minthostachys mollis (Kunth) Griseb Vaught var. mollis collected in January 2008 at Tuñame, Trujillo State, Venezuela, were separated and identified by GC-MS analysis. The essential oil was obtained by hydrodistillation and thirteen components (98.5% of the sample) were identified by comparison with the Wiley GC-MS library data base. The two major components were pulegone (55.2%) and trans-menthone (31.5%). The essential oil showed a significant inh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0
13

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 10 publications
0
9
0
13
Order By: Relevance
“…Is known by various popular names and has di erent medicinal uses. In Venezuela, M. mollis is known as oreganote and is prepared as tea and used to treat infectious diseases of children, as well as for rheumatism [2]. In Peru, the most well-known name of M. mollis is "muña", but in some regions it is also known as "ishmuña", "tento", "tinto" and "champca"; Traditionally it is used for the treatment of cough, bronchitis, stomach ulcer, gastritis, stomach and intestinal spasm, cold, headache, intestinal parasitism and as digestive [3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…Is known by various popular names and has di erent medicinal uses. In Venezuela, M. mollis is known as oreganote and is prepared as tea and used to treat infectious diseases of children, as well as for rheumatism [2]. In Peru, the most well-known name of M. mollis is "muña", but in some regions it is also known as "ishmuña", "tento", "tinto" and "champca"; Traditionally it is used for the treatment of cough, bronchitis, stomach ulcer, gastritis, stomach and intestinal spasm, cold, headache, intestinal parasitism and as digestive [3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…Other traditional uses of Minthostachys include biopesticides (antimycotic and antiparasitic, against flea infestations) and for the protection of stored potato and oca tubers from aphids and pests [6,7]. In recent years, there have been numerous research studies on Minthostachys oils to provide scientific evidences on their medicinal properties [8][9][10][11]. For instance, the main components of Minthostachys verticillata (M. verticillata) essential oil, namely pulegone (63.4%), menthone (15.9%), and limonene (2.1%), have been linked immediate-type allergic reactions in vitro and in vivo [8].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, the main components of Minthostachys verticillata (M. verticillata) essential oil, namely pulegone (63.4%), menthone (15.9%), and limonene (2.1%), have been linked immediate-type allergic reactions in vitro and in vivo [8]. Montironi et al (2016) have shown the bactericidal efficacy of M. verticillata essential oil against Streptococcus uberis strains isolated from bovine mastitis [9], while the essential oil of Minthostachys mollis (M. mollis) that largely contained pulegone (55.2%) and trans-menthone (31.5%) showed significant efficacy against Gram-positive and Gram-negative bacteria, especially Bacillus subtilis and Salmonella typhi, at 4 µg/mL [10]. A natural product, (−)-(1S,2R,3R,4S)-1,2-epoxy-1-methyl-4-(1-methylethyl)-cyclohex-3-yl acetate, isolated from the volatile constituents of Minthostachys tomentosa exhibited significant insecticidal activity against Oncopeltus fasciatus, whereas its synthetic form was found inactive [11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pharmacopoeia, 2009;European Pharmacopoeia, 2007) (PRIMO et al, 2001). O óleo de M. mollis apresentou teores de pulegona e mentona de 55,2 e 31,5 %, respectivamente (MORA et al, 2009). Estes resultados confirmam outras pesquisas, que demonstraram que os terpenos são responsáveis pela atividade antibacteriana e antifúngica (KARAMAN et al, 2003;SAHIN, 2002;GULLUCE et al, 2007).…”
Section: Obtenção Do óLeo Essencialunclassified